Forest Restoration at Berenty Reserve, Southern Madagascar: A Pilot Study of Tree Growth Following the Framework Species Method - Rubin Sagar; Ariadna Mondragon-Botero; Francine Dolins; Bryn Morgan; Thuy Phuong Vu; Janet McCrae; Vanessa Winchester (Land, 2021)
Forest conservation and restoration are urgently needed to preserve key resources for the endemic fauna of dry southern Madagascar. This is a priority in the shrinking, seasonally dry forest of Berenty, a private reserve in Southern Madagascar. However, to provide a basis for forest restoration, a study of tree growth and regeneration in this unique biome is essential. A three-year planting program of native and endemic species was initiated in 2016. Three trial plots were established in forest gaps, with varying microclimates and soil conditions: one on the riverside, one in the mid-forest and the third in a degraded dryland area. We planted 1297 seedlings of 24 native tree species with plantings spaced at 1 m and 1.5 m and measured their height and stem diameters and recorded seedling mortality. We also recorded plant recruitment on the plots from the nearby forest. The main findings were that growth was best on the mid-forest plot planted at 1 m. Seedling mortality was highest on the riverside plot for the 1 m seedlings and least in the mid-forest at both planting distances. Recruitment was highest in the mid-forest at both planting distances and high also at 1.5 m by the river. These results are intended to aid future forest restoration on the Reserve and may serve as a reference for restoration of other dry forests in Madagascar. Finally, since species identification is central to the project, we collected, prepared and catalogued tree specimens to form a reference collection in an herbarium under construction in a new Research Centre at the reserve.